(untitled) (Journal of the College of Basic Education, 2026)
This research addresses the issue of cheating in exams from various perspectives. It starts by defining cheating both linguistically and technically, describing it as presenting falsehood as truth or deceiving others in advice or dealings. In the context of exams, cheating refers to any unauthorized attempt to gain academic success without genuine effort. The study explores reasons behind cheating, including weak academic performance, fear of failure, lack of preparation, inadequate supervision, favoritism from teachers, and the advancement of modern cheating methods like smartphones and Bluetooth. It details traditional methods of cheating (e.g., hidden notes, writing on desks) and modern techniques (e.g., texting answers, teacher complicity From an Islamic perspective, cheating is strictly forbidden by all major Islamic scholars, based on Quranic verses and the Hadith (e.g., “Whoever cheats us is not one of us”). Cheating is seen as a form of betrayal, injustice, and societal harm, especially when it leads to unqualified individuals occupying important positions) Online cheating is equally prohibited, as the method of delivery does not alter the moral ruling. Assisting in cheating, whether by fellow students, teachers, or others, is also considered sinful and falls under aiding in wrongdoing .The conclusion emphasizes that exam cheating not only harms the individual but also jeopardizes the credibility and efficiency of society, marking it as a grave sin that must be avoided